Analisis Dampak Perceraian Orang Tua Terhadap Perkembangan Sosial dan Emosional Siswa - Yuningsih, Nina (Asatidzuna | Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
The purposes of this study are: 1) To find out and analyze the social development of broken home students due to divorce at SDN 4 Sindangpalay when they are in the school environment. 2) To find out and analyze the emotional development of broken home students due to divorce at SDN 4 Sindangpalay while in the school environment. The research method used is descriptive qualitative method with a case study approach. Through a series of research processes that can finally be poured into research results and elaborated in the discussion, it can be concluded that the social and emotional development of broken home students due to divorce at SDN 4 Sindangpalay is as follows. The social development of broken home students due to divorce at SDN 4 Sindangpalay can be categorized as good because even though the family is no longer together, the parents of broken home students are able to provide guidance in interactions within the family environment so that student interaction in the school environment is also good. The emotional development of broken home students due to divorce at SDN 4 Sindangpalay can be categorized as good because even though the family is no longer together, the parents of broken home students are able to manage emotions in parenting in the family environment so that the management of student emotions in the school environment is also good